Dentofacial injuries in commercial motorcycle accidents in Cameroon: pattern and cost implication of care - Agbor, Ashu Michael (Afr Health Sci, 2014)
OBJECTIVE: To assess the pattern of dentofacial injuries in commercial motorcycle accidents among riders and passengers in Cameroon. METHODS: This was a hospital based study conducted in 6 out of 10 regional capitals in the months of December 2011 to September 2012. Analyzed information included age, gender, residence, role on the motorcycle (rider or passenger), type, pattern and month of injury, cost, duration and patient's perception about the cost of treatment. RESULTS: A total of 387 patients were studied with majority of the patients being 21–30 years (39.8%), males (63.8%), passengers (57.3%) and urban dwellers (85.8%). Most of the injuries occurred in December (20.7%), January (19.4%) and February (20.2%). Soft tissue injuries were most frequent (91.2%) followed by trauma to the teeth (83.5%), of which 62.3% were tooth loss. Mandibular fracture was commoner than maxillary fracture; (45% versus 25.3%). A total of 44.2% of patients received their treatment as in-patients. The treatment of the dentofacial injuries among 64.3% of the patients lasted for more than a month. A total of 51.9% of the patients spent 100,000 francs ($200) or more for their treatment. More than half (51.4%) of the patients perceived the cost of treatment as expensive. CONCLUSION: Dentofacial injuries in commercial motorcycle accidents necessitated hospital admission and lengthy treatment time with high attendant cost. Preventing these injuries will serves as a form of poverty reduction as money that will be used by the victim to better their life is not used to correct deformities or treat injuries.